2020
DOI: 10.1186/s12909-020-02201-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of smartphone-based Mobile learning versus lecture-based learning for instruction of Cephalometric landmark identification

Abstract: Background Considering the increasing popularity of electronic learning, particularly smartphone-based mobile learning, and its reportedly optimal efficacy for instruction of complicated topics, this study aimed to compare the efficacy of smartphone-based mobile learning versus lecture-based learning for instruction of cephalometric landmark identification. Methods This quasi-experimental interventional study evaluated 53 dental students (4th year) in two groups of inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The included studies consist of 27 RCTs, 1 cluster RCT, 8 quasi-experimental studies, 15 interventional cohort studies, and 1 cross-sectional study, which was published between 2011 and 2020. Major portion of the studies (36/52) were performed in developed countries namely USA (n = 10) [18,21,23,24,32,34,38,42,50,60], UK (n = 7) [37,43,44,[47][48][49]52], South Korea (n = 5) [53,[58][59][60][61], Brazil (n = 4) [15,25,40,45], Germany (n = 3) [17,19,63], Spain (n = 3) [29,55,56], Turkey (n = 2) [22,54], Chile (n = 2) [9, 51], while the remaining 10 studies were from France [16], Australia [20], China [27], Iran (n = 4) [14,28,30,41], Rwanda [57], India [33], Taiwan [35], Canada [36], Pakistan [8], Thailand…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies consist of 27 RCTs, 1 cluster RCT, 8 quasi-experimental studies, 15 interventional cohort studies, and 1 cross-sectional study, which was published between 2011 and 2020. Major portion of the studies (36/52) were performed in developed countries namely USA (n = 10) [18,21,23,24,32,34,38,42,50,60], UK (n = 7) [37,43,44,[47][48][49]52], South Korea (n = 5) [53,[58][59][60][61], Brazil (n = 4) [15,25,40,45], Germany (n = 3) [17,19,63], Spain (n = 3) [29,55,56], Turkey (n = 2) [22,54], Chile (n = 2) [9, 51], while the remaining 10 studies were from France [16], Australia [20], China [27], Iran (n = 4) [14,28,30,41], Rwanda [57], India [33], Taiwan [35], Canada [36], Pakistan [8], Thailand…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Among that, one RCT conducted by Noll et al, [17] compared the effectiveness of augmented reality mobile application vs. mobile application and concluded that augmented reality mobile application was more effective in increasing the knowledge level than mobile application without augmented reality. 8 studies [5 RCTs [16,23,[53][54][55], 1 quasi-experimental study [30], and 2 interventional cohort studies [32,63]] reported that mobile applications were not effective in improving knowledge among study participants. Among that, one RCT conducted by Kim et al, 2018 [53] compared the effectiveness of interactive mobile application vs non-interactive mobile application and concluded that there is no significant difference in the knowledge level improvement between the two groups.…”
Section: Effect Of Intervention On Knowledge Of Hcpsmentioning
confidence: 99%
“…In addition, the experimental group attained significantly higher examination scores than the control group. The learning material in the mobile application concerning infection control knowledge included cephalometric landmark identification, dental treatment procedures, four‐handed techniques, and so on 6,7 . Researchers have reported that learning using mobile devices is effective in not only promoting learners’ motivation and learning participation but also in improving their knowledge 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, students majoring in dental healthcare were provided with education via a digital‐based mobile application rather than the traditional form, and the learning effect for the subject was found to be higher. In addition, students reported positive attitudes toward m‐learning 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Learning with mobile technologies in educational activities, called m-learning, 4 provides learning environments supported by electronic devices such as smartphones, tablets and laptops. 5 In dentistry, mobile applications have been used to assist clinical practice and m-learning 4,6 due to its easy portability and instant access to information, especially in offline modes. 7,8 The literature has highlighted relevant results from the use of ICTs as auxiliary tools in the formation of knowledge and support in the learning of dentistry.…”
Section: Introductionmentioning
confidence: 99%